Exploring Inner Dialogue in Counsellor Education - Paré, David; Lysack, Denise Mishka (Canadian Journal of Counselling and Psychotherapy, 2007)
The overt aspects of dialogue, especially the spoken exchange, are the focus of most counsellor education interventions. However, in addition to its visible and audible aspects, counselling conversation also features covert dimensions. This article describes an educational exercise designed to heighten counsellors’ awareness of one of these covert elements—counsellors’ inner dialogue. After a review of some theoretical views regarding the dialogic self, a counselling exercise devoted to an exploration of inner dialogue is described. Specific examples of dialogic exchanges and students’ comments on them illustrate the diversity of inner conversation. The article concludes with some suggested variations on the exercise for counsellor educators.